TECTONIC POSITION AND ORIGIN OF VOLCANOSEDIMENTARY ROCKS OF THE POLYARNYI UPLIFT (SOUTH ANYUI SUTURE, WESTERN CHUKOTKA) - Sokolov S.D.; Tuchkova M.I.; Bondarenko G.E.; Leyer P. (My University, 2006)
The South Anyui Suture (SAS) resulted from the closure of a past oceanic basin and subsequent collision between the North American and North Asian continents. Many geological aspects of this essential tectonic element of Mesozoides in Northeast Russia remain unclear so far. This concerns, first, the problem of the existence period of the paleoceanic basin. In this connection, the structural position, age, and origin of relatively widespread volcanosedimentary rocks are very important issues.
Keywords: South Anyui Suture; Chukotka